Potensi Google Trends sebagai Alat untuk Memantau Keresahan Masyarakat selama Pandemi COVID-19 - Muanifah, Erna Zuliana; Sukendra, Dyah Mahendrasari (Indonesian Journal of Public Health and Nutrition, 2023)
Background: The number of confirmed cases of COVID-19 has increased since it was first discovered in Indonesia. It is important to know that public concerns and public awareness of the COVID-19 disease are needed to assist risk communication during the pandemic. Therefore, researchers want to know the potential of Google Trends to monitor public reaction during the COVID-19 pandemic. Methods: This research is a quantitative research using time series approach (1 Juni 2021-30 September 2021). The keyword related to COVID-19 disease used in this study is ‘corona’. Bivariate analysis using Spearman correlation test. Results: Based on the results of the Spearman correlation test, it shows that there is a correlation between the search trend for the term 'corona' and the number of new confirmed cases of COVID-19 in Central Java with an r count of +0.649 and a p value of 0.0001. Conclusion: There is a significant relationship between the search trend for the term 'corona' and the number of cases of COVID-19. This shows that the search for information related to COVID-19 may be able to monitor public reaction during the COVID-19 pandemic.